Progressive collapse resistance of precast concrete beam-column sub-assemblages with high-performance dry connections. (1st November 2019) - Qian, Kai; Liang, Shi-Lin; Fu, Feng; Fang, Qin
Highlights: Progressive collapse behavior of PC frames with high-performance dry connection was assessed. Load resisting mechanism of PC frames was compared with conventional RC frames. The effects of different column missing scenarios and connection details were quantified. Analytical analysis was carried out to de-composite the contribution of different mechanisms. Abstract: Due to its relatively lower integrity, precast concrete structures are considered to be more vulnerable to progressive collapse than cast-in-place concrete structures. However, to date, majority of existing studies on progressive collapse focused on cast-in-place concrete structures, little attentions were paid to precast concrete structures. Among existing precast concrete structures, unbonded post-tensioning precast concrete structure is one of innovation dry connection structural systems, which no casting at the connections on site. Its excellent seismic performance was recognized by many studies, while studies on its progressive collapse resistance were very few. To fill this knowledge gaps, in this paper, eight half-scaled unbonded post-tensioning precast concrete beam-column sub-assemblages with different connection configurations were tested through pushdown tests to investigate their capacities and resistance mechanisms to prevent progressive collapse. The test results demonstrated various behaviors of beam-column sub-assemblages with different connection types. It was found that, as the longitudinal reinforcements were discontinuous across the beam-column joint region in the beams, flexural action observed in the cast-in-place concrete frames was not mobilized for the specimens with purely unbonded post-tensioning connections. When the specimens installed top-seat angles at the beam-column interfaces, considerable flexural action capacity could be mobilized for load resistance. Moreover, it was found that the failure modes of the specimens are distinctly different to that of conventional reinforced concrete frames or precast concrete frames with cast-in-place joints. The characteristic of compressive arch action and tensile catenary action in tested specimens is quite different to that of conventional reinforced concrete frames.